Brief Research Report on Adolescent Mental Well-Being and School Closures During the COVID-19 Pandemic in Indonesia - Wiguna, Tjhin; Anindyajati, Gina; Kaligis, Fransiska; Ismail, Raden Irawati; Minayati, Kusuma; Hanafi, Enjeline; Murtani, Belinda Julivia; Wigantara, Ngurah Agung; Putra, Anggi Aviandri; Pradana, Kent (Frontiers in Psychiatry, 2020)
Being adolescence, The COVID-19 pandemic is challenging because it was influenced their developmental milestones. Therefore, this brief report is aimed to preliminary present several factors related to adolescents' mental well-being during COVID-19 pandemic in Indonesia. This was a cross sectional study and used online survey. During April 15 – May 10, 2020, there were 113 adolescents participated on this survey. SDQ was used to assess adolescent emotional and behavior problems; and specific life experience questionnaire was designed to collect other independents variables. All data was analyzed by using SPSS version 20 for Mac. There was 38.1% of adolescent was at risk on peer-relationship problems, 28.3% at risk on pro-social behavior problems, 15% at risk on conduct behavior and 10.6 % at risk on emotional problems. There was significantly association between having mental health information and conduct behavior (OR=10.34, 95%CI=1.27 – 78.86); Subjective anxiety due to COVID-19 pandemic and pro-social behavior problems (OR=2,37, 95% CI=1.00 – 5.63), parental support and total difficulties (OR=0.09, 95% CI=0.14 – 0.60) and pro-social behavior problems (OR=0.09, 95% CI= 0.01 – 0.82); friends support during COVID-19 pandemic and conduct behavior (OR=0.20, 95% CI=0.04 – 1.00) and pro-social behavior problems (OR= 0.14, 95% CI=0.02 – 0.75). This brief report showed that during phase 1 and 2 COVID-19 pandemic, adolescents were at risk for having emotional and behavior problems. Therefore, maintain a clear mental health information, keep them on connection with school by designing an optimal tele-education, tele-consultation and virtual activity programs to accommodate adolescents’ biopsychosocial needs.